IDEOLOGICAL STIGMATIZATION OF SCIENCE. THE CASE OF KNJIGA O KOSOVU BY DIMITRIJE BOGDANOVIĆ (Heritage, 2026)
Ideological bias was one of the greatest shortcomings of historiography from the time of socialist Yugoslavia. The strict control of the ruling communist party was the main reason why many important topics were inadequately covered or even completely avoided. Therefore, during the 1980s, after the death of Josip Broz, a large number of diverse books appeared, that caused controversy in both party and scholarly circles. Among them is  Knjiga o Kosovu by academician Dimitrije Bogdanović, which later, like its author, experienced a large number of politically motivated attacks. In addition to analyzing the book, the paper will reconstruct the context in which it was written, the author's motives for addressing the topic, and the reactions provoked by its publication. The paper is based on sources in the form of press and testimonies of contemporaries, as well as relevant scientific literature.
Keywords: Dimitrije Bogdanović, Knjiga o Kosovu, ideology, repression, historiography, communism.